2014
DOI: 10.1063/1.4861465
|View full text |Cite
|
Sign up to set email alerts
|

Long-infrared InAs-based quantum cascade lasers operating at 291 K (λ=19 μm) with metal-metal resonators

Abstract: Articles you may be interested inDouble metal waveguide InGaAs/AlInAs quantum cascade lasers emitting at 24μm Appl. Phys. Lett. 105, 121115 (2014); 10.1063/1.4896542 High temperature, single mode, long infrared (λ=17.8μm) InAs-based quantum cascade lasers Appl. Phys. Lett. 105, 111118 (2014); 10.1063/1.4895763 Room-temperature operation of 3.6 μ m In 0.53 Ga 0.47 As / Al 0.48 In 0.52 As quantum cascade laser sources based on intracavity second harmonic generation Appl. Phys. Lett. 97, 141103 (2010); 10.1063/1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These values for facet reflectivity and waveguide losses are similar to our previous results in Ref. 3. FP laser ridge resonators have been fabricated in a metal-metal waveguide geometry using the same protocol as in Ref.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…These values for facet reflectivity and waveguide losses are similar to our previous results in Ref. 3. FP laser ridge resonators have been fabricated in a metal-metal waveguide geometry using the same protocol as in Ref.…”
mentioning
confidence: 65%
“…1,2 As shown in Ref. 3, the low electronic effective mass in the InAs wells leads to extremely low threshold current densities and almost room-temperature (RT) operation at k > 19 lm. We have also shown that in this wavelength range metal-metal (MM) waveguides, 4 which are typically employed for THz lasers, 8 are very efficient and yield reasonable far-fields (FFs), contrary to what is experienced at THz frequencies.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…There has been a considerable academic and technological interest in (a) the epitaxial growth of III–V zinc‐blende (zb) type indium pnictides (e.g., InP, InAs, and InSb) and their alloys (e.g., InSb x (P x )As 1 − x ), (b) characterizing them with spectroscopic techniques, and (c) providing rapid feedback of their optical/electrical characteristics. Although InAs has exhibited important applications to engineer high speed electronics including low power field effect transistors and long‐wavelength photonic devices, the binary InSb and its ternary InSb x (P x )As 1 − x alloys are proven valuable alternatives to mercury cadmium telluride based 8–14 μm infrared (IR) detectors . For preparing appropriate structures to optimize device performance, it is essential to have an accurate knowledge of the site selectivty of n‐ and p‐type dopants .…”
Section: Introductionmentioning
confidence: 99%